Dinamika Produksi Informasi: Peran Citizen Journalism dan Media Lokal di Sumatera Barat (2010–2024) - Puja Febrian; Haldi Patra (Jurnal Kronologi, 2026)
This study examines the dynamics of information production in the social media era through the role of citizen journalism and the development of press history in West Sumatra during the period 2010–2024. The background of this study is based on the significance of digital technology development, which has transformed patterns of information production and dissemination that were previously controlled by professional journalists into a more participatory system in West Sumatra. The purpose of this study is to examine the role of citizen journalism, public involvement in producing information, and the development of press history up to the present in West Sumatra. The method used is the historical method, including heuristics, source criticism, interpretation, and historiography, utilizing primary sources in the form of digital social media archives in West Sumatra, interviews, and secondary sources from scholarly literature. The results of the study show that the development of the press in West Sumatra has changed along with the development of media technology, while the emergence of citizen journalism in West Sumatra has become part of this transformation, functioning as a fast initial source of information. In conclusion, the dynamic relationship between the development of the press and citizen journalism in West Sumatra indicates a shift in the structure of information production toward a more open system with increased public participation in the digital era.